Topological and lexical determination in particle verb constructions: INs and OUTs in second language processing - Geld, Renata (2007)
As a usage-based theoretical framework, cognitive linguistics should have a tremendous impact in second language acquisition research. One of the strongest aspects of this framework in terms of SLA research is its insistence on language being an experiential phenomenon intimately connected with other cognitive abilities. A large group of cognitive processes that were neglected in modular theories of language development are cognitive (learning) strategies. Language was seen as separate from other cognitive domains and learning mechanisms operating in the process of language acquisition were considered language specific. The research presented in this paper is based on the constructivist view of language (Langacker 1988, 2000 ; Tomasello 2003), and the results suggest that meaning construal can be used as evidence towards the connection of cognitive strategies in the acquisition of L2 and general cognitive processes present in L1. The aim of the research was to establish patterns in L2 processing, particularly those related to topological (Talmy 2000) and lexical determination in the meaning construal of English particle verbs (cf. Rudzka-Ostyn 2003). The paper discusses the results obtained from quantitative and qualitative research into strategic construal, i.e. meaning construal in second language processing (Geld in press). The subjects were a group of 100 speakers of English as a second language (68 speakers of Croatian as L1 and 32 speakers of Spanish as L1). The language material consisted of 20 particle verbs combining light (go, take and put) and heavy (call, cut, break, draw, pull, shut and write) lexical parts with in and out. The 46 meanings selected for the research material were those qualified as obscure by a triangulation study conducted prior to the main stage of the research. The subjects were asked to make sense of the phrasal verb constructions and try to explain what it is in each construction that produces specific meaning(s). There were two basic hypotheses: a) topological determination is expected with particle verbs consisting of light lexical parts, b) a more “ balanced” determination is expected with particle verbs containing heavy lexical parts. Preliminary results reveal the following tendencies: 1) stronger topological determination with particle verbs containing light lexical parts, 2) higher frequency of compositional meanings with particle verbs containing heavy lexical parts, 3) higher frequency of compositional meanings in speakers with higher language proficiency, 4) more frequent topological determination in speakers with higher language proficiency. The paper offers detailed description of these tendencies, focusing on the patterns found to determine the strategic construal of in and out.
Projekt MZOS
ENG